2022
DOI: 10.1108/jamr-10-2021-0343
|View full text |Cite
|
Sign up to set email alerts
|

The impact of LinkedIn posts on employer brand perception and the mediating effects of employer attractiveness and corporate reputation

Abstract: PurposeThe aim of this study is to identify the relationship between employee-generated content (EGC) and firm-generated content (FGC) in the form of LinkedIn posts, employer brand perception, and the effect of employer's attractiveness and corporate reputation on this relationship.Design/methodology/approachThis study comprises two phases. In phase 1, the focus was on stimuli selection through an online questionnaire on favourability. In phase 2, for the main study, data were gathered through an online survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…LinkedIn, in particular, is widely used in recruitment and EB efforts (Content Stadium, 2022). Joglekar and Tan (2022) demonstrated that employee-generated content and firm-generated content in the form of LinkedIn posts positively influenced employer perception, with this relationship being mediated by organizational attractiveness and corporate reputation. Their findings suggest that companies can strategically utilize LinkedIn to encourage employee advocacy initiatives, attracting new talent and enhancing organizational attractiveness and reputation.…”
Section: Conceptual Backgroundmentioning
confidence: 95%
“…LinkedIn, in particular, is widely used in recruitment and EB efforts (Content Stadium, 2022). Joglekar and Tan (2022) demonstrated that employee-generated content and firm-generated content in the form of LinkedIn posts positively influenced employer perception, with this relationship being mediated by organizational attractiveness and corporate reputation. Their findings suggest that companies can strategically utilize LinkedIn to encourage employee advocacy initiatives, attracting new talent and enhancing organizational attractiveness and reputation.…”
Section: Conceptual Backgroundmentioning
confidence: 95%
“…The platform serves as a prominent identification point due to the constant visibility of the link between employees and their employers (Van Zoonen et al ., 2018), which automatically turns employees into ambassadors. Consequently, previous research has mainly been based on human resource (HR) management studies, which have analyzed how employee ambassadorship on LinkedIn influences the employer’s brand (Da Motta Veiga et al ., 2020; Joglekar and Tan, 2022).…”
Section: Research On Employee Ambassadorship and Powermentioning
confidence: 99%
“…It helps in facilitating interactive information, user-created content and collaboration (Elefant, 2011). Since the proliferation of social media, organizations use SNS such as LinkedIn, Twitter and Facebook to publicize positions (Joglekar and Tan, 2022) and advertise benefits provided to the employees. They are preferred over classic printed advertisements and face-to-face interaction due to their unlimited use, shorter response time and minimal search cost (Sivertzen et al , 2013, p. 475).…”
Section: Developing Hypothesesmentioning
confidence: 99%
“…More pertinent to the Indian context, the role of employer branding in building positive perceptions among job seekers is an under-researched (Khan, 2017) and a more pressing issue, particularly in an emerging economy like India (Sharma and Prasad, 2018). India, with its distinctive demographic dividend and budding economy, is an apparent choice among employers in the world to fulfill their human resource needs (Joglekar and Tan, 2022). This makes the present study of paramount importance and therefore aims to perform an empirical analysis to validate the proposed relationships.…”
Section: Introductory Backgroundmentioning
confidence: 99%